Effectiveness of a theory-based breastfeeding promotion intervention on exclusive breastfeeding in China: A randomised controlled trial. (November 2016) - Gu, Yanhong; Zhu, Yu; Zhang, Zhihong; Wan, Hongwei
Abstract: Objective: To investigate the effectiveness of a designed intervention programme on the promotion of exclusive breast feeding during 6 months post partum among Chinese primiparous women, based on the theory of planned behaviour. Design: Randomised controlled trial. Setting: A tertiary hospital in Shanghai, China. Participants: Chinese primiparous women who were able to breastfed their babies and companied by either husband or mothers. Intervention: Participants were randomly divided into the intervention and control group. On the basis of the theory of planned behaviour, mothers in the intervention group received the TPB-based intervention programme, including individual instruction, group education and telephone counselling, whereas both the intervention and control group continued to receive routine nursing care. Measurements and Findings: Data were collected between October 2013 and June 2014. Initially, 352 participants were included. However, 67 of them dropped out or were lost to follow-up. Finally, 285 participants were included into the analysis, including 157 participants in the intervention group and 128 participants in the control group. Though some bias might exist, rates of exclusive breast feeding were consistently and significantly higher in the intervention group than the control group at 3 days (40.1% versus 10.9%, P <0.001), 6 weeks (57.3% versus 29.7%, P <0.001), 4 months (56.7% versus 15.6%, P <0.001) and 6 months post partum (42.0% versus 10.2%, P <0.001). Conclusion and implications: The TPB-based breast-feeding promotion intervention is effective in improving exclusive breast-feeding rates in primiparous women. Although the current intervention that provides continued support during the hospitalisation and follow-up at home, problems remains in the workplaces.